In Situ Enzyme Immobilization with Oxygen‐Sensitive Luminescent Metal–Organic Frameworks to Realize "All‐in‐One" Multifunctions. Issue 21 (15th March 2019) - Xu, Yuzhi; Liu, Si‐Yang; Liu, Junling; Zhang, Li; Chen, Danping; Chen, Jun; Ma, Yingjun; Zhang, Jie‐Peng; Dai, Zong; Zou, Xiaoyong
Abstract: Invited for the cover of this issue are Jie‐Peng Zhang, Zong Dai, and co‐workers at Sun Yat‐sen University. The image depicts the harmonious and synergetic combination of MAF‐2 and glucose oxidase (just like the Tai Chi in the background). Read the full text of the article at 10.1002/chem.201806146 . Abstract : " Since metal–organic frameworks (MOFs) and enzymes both have exhibited diverse functions and properties, we hope this exploratory work will inspire more research on utilizing the multifunctions of MOFs for enzyme‐related applications ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5463 ff. (DOI: 10.1002/chem.201806146 ).